Would Educational Inequality Aggravate Environmental Pollution? —Evidence From Spatial-Based Panel Analysis in China - Liu, Xin; Liu, Huige; Yang, Jian (Frontiers in Environmental Science, 2022)
Educational inequality has always been the most discussed topic in China, and it may also result in a series of social problems with an expansionist trend. More specifically, education issues have possible influences on environmental activities, while some of them are unaccounted for. To fill in the gaps where few studies focus on the relationship between inequality and environmental pollution, we empirically study the impact of educational inequality on air quality as fine particulate matter (PM2.5) using panel data from 30 provinces and cities in China. Based on an analysis of the imbalanced distribution of educational level and individual behaviors, we theoretically infer that deepening educational inequality weakens individual environmental behaviors and thus aggravates environmental quality. We undertake a panel data analysis and, to a certain extent, confirm our expected negative relation. To precisely estimate the causality, we consider the spatial spillover effect to be a key property of air pollutants. We find that widening educational inequality, which is measured by the Gini coefficient of education, causes environmental deterioration. More specifically, educational inequality will inhibit the level of regional technological innovation, thereby damaging environmental quality. In addition, we estimate a series of other variables about education and find that enhancing educational expenditure and educational resources at the regional level of education would improve air quality. Our results suggest that even from an environmental perspective, governments should take measures to prevent the potential excessive centralization of educational resources. Efforts to achieve equality in education engender not only social fairness but also practical significance for environmental protection.